The anti-inflammatory protein TNFAIP3/A20 binds the WD40 domain of ATG16L1 to control the autophagic response, NFKB/NF-κB activation and intestinal homeostasis. Issue 9 (2nd September 2019) - Serramito-Gómez, Inmaculada; Boada-Romero, Emilio; Slowicka, Karolina; Vereecke, Lars; Van Loo, Geert; Pimentel-Muiños, Felipe X.
ABSTRACT: The C-terminal domain of ATG16L1 includes 7 WD40-type repeats (WD40 domain, WDD) and is not required for canonical macroautophagy/autophagy. Instead, the WDD allows ATG16L1 to induce LC3/Atg8 lipidation in single-membrane compartments, although a detailed functional characterization of this region is still missing. In a recent report we identify the anti-inflammatory molecule TNFAIP3/A20 as a binding partner of the WDD. Such physical interaction allows mutual downregulation of the expression levels of both proteins, so that the absence of one of them causes upregulation of the other. This cross-regulation provides a molecular basis for a striking genetic interaction in mice where elimination of both molecules in the intestinal epithelium generates an aggressive inflammatory phenotype. In vitro studies reveal unexpected features of the functional interplay between ATG16L1 and TNFAIP3. ATG16L1 requires TNFAIP3 to sustain the canonical autophagic flux measured by SQSTM1/p62 degradation. The WDD mediates lysosomal degradation of TNFAIP3 promoted by ATG16L1, and also regulates the NFKB/NF-κB response. Therefore, our data reveal new roles of the WDD and TNFAIP3 in the regulation of autophagy, protein stability and inflammatory signaling. More generally, we identify the interaction between ATG16L1 and TNFAIP3 as a signaling hub that integrates different pathways with important implications for intestinal homeostasis.